Establishment and maintenance of parasegmental compartments. - Hughes, S.C.; Krause, H.M. (Development, 2001)
Embryos of higher metazoans are divided into repeating units early in development. In Drosophila, the earliest segmental units to form are the parasegments. Parasegments are initially defined by alternating stripes of expression of the fushi-tarazu and even-skipped genes. How fushi-tarazu and even-skipped define the parasegment boundaries, and how parasegments are lost when fushi-tarazu or even-skipped fail to function correctly, have never been fully or properly explained. Here we show that parasegment widths are defined early by the relative levels of fushi-tarazu and even-skipped at stripe junctions. Changing these levels results in alternating wide and narrow parasegments. When shifted by 30% or more, the enlarged parasegments remain enlarged and the reduced parasegments are lost. Loss of the reduced parasegments occurs in three steps; delamination of cells from the epithelial layer, apoptosis of the delaminated cells and finally apoptosis of inappropriate cells remaining at the surface. The establishment and maintenance of vertebrate metameres may be governed by similar processes and properties.